Determining the optimal isoleucine:lysine ratio for the 25 to 50 lb pig - Bergstrom, J.R.; Loughmiller, J.A.; Musser, R.E.; Nessmith, W.B.,Jr.; Nelssen, Jim L.; Tokach, Michael D.; Goodband, Robert D.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A 21-day growth trial was conducted to determine the isoleucine: lysine ratio necessary to optimize growth performance of the 25 to 50 lb nursery pig reared in a segregated early-weaning (SEW) system. Ten experimental diets, including two levels of lysine (.75% and 1.10% digestible lysine) and five apparent digestible isoleucine:lysine ratios (45, 50, 55, 60, and 65%), were used in a 2 x 5 factorial arrangement. Growth performance was improved by feeding 1.10% rather than .75% digestible lysine. Also, results indicated that the apparent digestible isoleucine requirement for the SEW-reared, 25 to 50 lb pig is approximately .50% of digestible lysine.
Keywords: Swine; Early-weaned pigs; Amino acids; Isoleucine